2018
DOI: 10.3390/su10093303
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Land Use Changes in a Rapidly Developing City during 1990–2017 Using Satellite Imagery: A Case Study in Hangzhou Urban Area, China

Abstract: As one of the rapidly-developing mega cities in China, Hangzhou has experienced great land use change during the past three decades. By analyzing land use change in designated period, it is beneficial to understand urbanization process in Hangzhou, and undertake further urban management and urban planning. In this study, the land use change from 1990 to 2017 in Hangzhou urban area was detected by a method of supervised classification with Landsat TM images from 1990, 1997, 2004, 2010 and 2017, and analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
(65 reference statements)
0
8
0
1
Order By: Relevance
“…Land use/land cover (LULC) changes are presently becoming issues of great concern regionally and globally due to numerous environmental challenges. The rapid increase in population and the expansion of urban areas due to urbanization has contributed immensely to the change in land use/land cover patterns and the conversion of fertile land and vegetation to land use of different functions [1][2][3]. The continuous transformation of land uses and widespread deforestation has continuously led to multiple scales of emerging environmental issues with severe effects on the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Land use/land cover (LULC) changes are presently becoming issues of great concern regionally and globally due to numerous environmental challenges. The rapid increase in population and the expansion of urban areas due to urbanization has contributed immensely to the change in land use/land cover patterns and the conversion of fertile land and vegetation to land use of different functions [1][2][3]. The continuous transformation of land uses and widespread deforestation has continuously led to multiple scales of emerging environmental issues with severe effects on the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Mamminasata Metropolitan City, it has a tendency to grow dynamically in line with the dynamics of demographic, economic and physical-spatial development. The authors of [26] confirmed that exurban development is defined a discontinuous, low-density expansion into fringe land, emphasizing dependency on private mobility, soil consumption, and depolarized economic structures. Physically, Metropolitan Mamminasata urban areas are growing expansively towards the outskirts, even beyond the administrative boundaries of their territories.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, to have the highest accuracy in land use land cover (LULC) spatial data, the geo-referenced based high Resolution of previous governmental detailed maps and authorized satellite images [ 71 ] (referred to in table 3.1) of different interval years of Karachi by responsible authority ( http://www.kmc.gos.pk/ ) were used in this research. Simultaneously, different geometric-based scientific models have been widely applied in several studies to assess the land use/land cover transformation internationally, such as the multi-agent System [ 72 , 73 ], Cellular Automata (CA) Model [ 74 , 75 ], Markov chain analysis (also called transition matrix) [ 63 , 76 , 77 ], Expert Models [ [78] , [79] , [80] , [81] ], Land Change Modeler (LCM) [ 82 ], Logistic Regression [ [83] , [84] , [85] ], and Evolutionary Models [ [86] , [87] , [88] ], etc. However, an integrated Cellular Automata Markov (CA-Markov) Model [ 19 , 68 , [89] , [90] , [91] , [92] ] has been preferred by academia while conducting land use land cover (LULC) studies around the world due to virtue of its spatiotemporal attributes and perfect predictions [ 19 , 92 ].…”
Section: Literature Reviewmentioning
confidence: 99%